Pseudoautosomal deletions encompassing a novel homeobox gene cause growth failure in idiopathic short stature and Turner syndrome - Rao, Ercole; Weiß, Birgit; Fukami, Maki; Rump, Andreas; Niesler, Beate; Mertz, Annelyse; Muroya, Koji; Binder, Gerhard; Kirsch, Stefan; Winkelmann, Martina; Nordsiek, Gabriele; Heinrich, Udo; et al. (Nature genetics, 1997)
Growth retardation resulting in short stature is a major concern for parents and due to its great variety of causes, a complex diagnostic challenge for clinicians. A major locus involved in linear growth has been implicated within the pseudoautosomal region (PAR1) of the human sex chromosomes. We have determined an interval of 170 kb of DNA within PAR1 which was deleted in 36 individuals with short stature and different rearrangements on Xp22 or Yp11.3. This deletion was not detected in any of the relatives with normal stature or in a further 30 individuals with rearrangements on Xp22 or Yp11.3 with normal height. We have isolated a homeobox-containing gene (SHOX} from this region, which has at least two alternatively spliced forms, encoding proteins with different patterns of expression. We also identified one functionally significant SHOX mutation by screening 91 individuals with idiopathic short stature. Our data suggest an involvement of SHOX in idiopathic growth retardation and in the short stature phenotype of Turner syndrome patients.
Gesehen am 29.03.2021